Evaluating Recycled PET as an Alternative Material for the Construction Sector Towards Sustainability - Omar Albatayneh; Mohammad Nadeem Akhtar (Salehan Institute of Higher Education, 2024)
Addressing the environmental threat of Polyethylene Terephthalate (PET) waste is critical for sustainable development. Despite PET's prevalence in everyday products, its improper disposal endangers environmental health. This study targets a pivotal gap in current research. PET waste's potential as a sustainable building material will be thoroughly evaluated, focusing on whether recycling PET waste is feasible. In the construction industry, it can be a substitute for natural sand and an additive in cement. This study contributes to a dual-purpose solution: mitigating environmental pollution and innovating in construction material science. The systematic literature review (SLR) delves into existing studies, focusing on PET's impact on concrete properties when substituting natural sand at ratios of 5% to 20% and as a cement additive at 0.5% to 2% by weight. The findings revealed that up to a 10% PET replacement enhances compressive strength, highlighting a sustainable pathway for construction practices. However, replacements above 10% show a reduction in strength, indicating an optimal substitution threshold. Moreover, incorporating PET additives at 1% by cement weight optimizes flexural strength, underscoring the material's viability in enhancing structural integrity. This study sheds light on PET waste's application in reducing environmental impact and proposes a viable, eco-friendly alternative for construction materials. The recommendation for further research underscores the necessity to refine PET's application in construction, aiming to bridge the knowledge gap and encourage sustainable future innovations. Doi: 10.28991/CEJ-2024-010-04-020 Full Text: PDF